1998
DOI: 10.1063/1.477697
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of charged defects in a series of α,α′-dimethyl end-capped oligothiophenes induced by chemical doping with iodine

Abstract: We present the results of a detailed study carried out on a few α,α′-dimethyl end-capped oligothiophenes which have been in situ doped with dry iodine vapors, at different concentrations. The doping process of these well sized oligomers (from dimer to hexamer) has been monitored by using Fourier transform infrared absorption and Fourier transform raman scattering spectroscopies. These data, when combined with the vibrational full assignment of the oligomers in the neutral state and the electronic absorption ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 42 publications
8
71
0
Order By: Relevance
“…Consequently, in these stilbene derivatives the ICT results in a more pronounced perturbation of the acceptor subunit than of the donor subunit with respect to the nonpolar system, generating two different molecular domains within the π-conjugated bridge (one with a partial quinonoid character and the other with an almost pure aromatic character). [54,55] Natural bond orbital analysis NBO analysis has proved to be an effective tool for chemical interpretation of hyperconjugative interaction and electron density transfer (EDT) from filled lone electron pairs of the n(Y) of the 'Lewis base' Y into the unfilled anti-bond σ * (X-H) of the 'Lewis acid' X-H in X-H· · ·Y hydrogen bonding systems. [56] To elucidate and explain inter-and intra molecular hydrogen bonding, ICT, rehybridization, delocalization of ED and cooperative effect due to n (O) → σ * (C-H), the NBO analysis has been performed and the corresponding results are presented in Tables S4 and S5 (Supporting Informations).…”
Section: Optimized Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, in these stilbene derivatives the ICT results in a more pronounced perturbation of the acceptor subunit than of the donor subunit with respect to the nonpolar system, generating two different molecular domains within the π-conjugated bridge (one with a partial quinonoid character and the other with an almost pure aromatic character). [54,55] Natural bond orbital analysis NBO analysis has proved to be an effective tool for chemical interpretation of hyperconjugative interaction and electron density transfer (EDT) from filled lone electron pairs of the n(Y) of the 'Lewis base' Y into the unfilled anti-bond σ * (X-H) of the 'Lewis acid' X-H in X-H· · ·Y hydrogen bonding systems. [56] To elucidate and explain inter-and intra molecular hydrogen bonding, ICT, rehybridization, delocalization of ED and cooperative effect due to n (O) → σ * (C-H), the NBO analysis has been performed and the corresponding results are presented in Tables S4 and S5 (Supporting Informations).…”
Section: Optimized Geometrymentioning
confidence: 99%
“…[55,80,84] The C-N stretching mode are observed in the IR at 892 and at 897 cm −1 in the Raman spectrum. The absorption bands arising from other skeletal mode have been identified and assigned.…”
Section: Skeletal Modes Vibrationsmentioning
confidence: 99%
“…Throughout our study, MP2/aug-cc-pVTZ geometries were used that are very close to the MP2/AVTZ geometries of the original study, which were found to agree well with experimental data. 32 Tests with MP2/AVTZ and MP2/aug-cc-pVQZ geometries showed very small effects of 0.1 to 0.2 kcal/mol on the calculated interaction energies for both CCSD(T) and FNDMC.…”
Section: Computational Detailsmentioning
confidence: 99%
“…23,28 In the case of T2VT2 the corresponding Raman-active vibration was observed at 1539 cm -1 and assigned, on the basis of the RHF/6-31G** theoretical eigenvectors, as a totally symmetric ν as (CdC) mode mainly localized on the two outer rings. For (T2VT2) 2, line A disperses 20 cm -1 downward with respect to T2VT2.…”
Section: (T2vt2) 2 In Neutral Statementioning
confidence: 99%